2022
DOI: 10.3389/fpubh.2022.850550
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health-Related Quality of Life Among Narcotic and Stimulant Users Referred to Maintenance Methadone Therapy Centers in Ahvaz City: Iran

Abstract: IntroductionWe aimed to assess quality of life related to oral health in narcotic or stimulant users those were referred to maintenance methadone therapy (MMT) centers in Ahvaz City, Iran.MethodsIt was a cross-sectional study based on exploratory approach which has conducted on 187 narcotic and stimulant users in Ahvaz city; during 15th May till September 2020. Data was selected by available non-random sampling method. The data collection tools included the demographic variables and the standard OHIP-14 questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
(18 reference statements)
1
1
0
Order By: Relevance
“…This study showed significant results for the types of drugs consumed. 32 The results of this study were in line with the results of Fei et al's study which found that the quality of life of respondents who used methadone for longer time did not experience a greater increase compared to respondents who used methadone relatively in a shorter time. Other studies have also shown similar results that long-term use of methadone showed a less consistent quality of life.…”
Section: Discussionsupporting
confidence: 91%
“…This study showed significant results for the types of drugs consumed. 32 The results of this study were in line with the results of Fei et al's study which found that the quality of life of respondents who used methadone for longer time did not experience a greater increase compared to respondents who used methadone relatively in a shorter time. Other studies have also shown similar results that long-term use of methadone showed a less consistent quality of life.…”
Section: Discussionsupporting
confidence: 91%
“…Secondly, this selection bias is essentially unavoidable when using research registries but should be considered when interpreting results. Finally, there are potential factors that can influence the relationship between oral health literacy and the oral health-related quality of life, such as education and socio-economic status and other sources of bias, which were not considered in the study criteria and may have affected the results ( 31 ).…”
Section: Discussionmentioning
confidence: 99%